Retórica y misoginia en la caracterización egoísta del héroe sentimental: Aquiles y Calisto - Peláez Benítez, M.ª Dolores (Dicenda. Estudios de lengua y literatura españolas, 2003)
The article studies Aquiles’ egoist characterization by analyzing the Power of Woman topos as it is developed in Aquiles and Policena’s sentimental story in the Roman de Troie’s Castilian version known as Versión de Alfonso XI del Roman de Troie (1350). Considering its ironic reading as well as the characters’ analysis, it stablishes a relationship between Aquiles and Calisto in La Celestina, whose egoist characterization distinguishes him from other sentimental heroes, and proposes Aquiles as a possible literary reference of Calisto’s egoist tipification.